Food viral recommendation mobile application using geolocation with auto recommendation places (EatNow!) / Nur Ain Zubari … [et al.] - Zubari, Nur Ain; Arshad, Mohamad Asrol; Md Rashid, Nor Aimuni; Buja, Alya Geogiana; Lemuel Kushan, Albin (Faculty of Computer and Mathematical Sciences, 2021)
Along the 21st Century, mobile applications become more rampant among the people. Nowadays, they keep depending on mobile apps to perform daily life. It includes when tourist unfamiliar to choose popular food in a particular area. EatNow! Mobile application will help ease the user find popular food based on user preferences. EatNow! Application is a viral food recommendation using geolocation with auto-recommendation places. With the implementation of geolocation, the application can suggest places based on the user 6s current location. The recommendation based on the 3 APIs, the Foursquare API, Google Places API, and OpenWeather API. EatNow! Apps recommend the places based on user preferences by using a rule-based system and user’s current location. The application’s effectiveness has evaluated by conducted functionality, usability, and accuracy testing. Findings show that EatNow! Application can help user find restaurants based on their preferences and the nearest user’s current location. In conclusion, EatNow! is useful for any users to find nearby food areas and save the time consumption to find food viral.